Bronchoscopic lavage for pulmonary aspiration: a case series - Wen, Tingting; Xiong, Bing; Mei, Chengjie; Song, Shengwen (AME Case Reports, 2026)
Background: Pulmonary aspiration of gastric contents is a life-threatening complication during anesthesia. Although immediate interventions are recommended, the role of bronchoscopic lavage remains controversial due to theoretical concerns about disseminating contaminants and limited clinical evidence.Case Description: We present four illustrative cases of high-risk patients who underwent bronchoscopic lavage following large-volume aspiration of gastric fluid, solid material, or bile. All patients showed immediate improvement in oxygenation and reduction in airway pressure after bronchoscopic lavage, with a total of 250–700 mL of normal saline instilled into the affected lobar bronchi. None developed severe complications such as aspiration pneumonia, severe acute respiratory distress syndrome (ARDS), or death. Notably, one patient with pre-existing lung injury due to necrotizing pancreatitis also recovered favorably. In the two patients with available follow-up imaging, there was no radiographic evidence of bronchoscopic lavage -induced consolidation or diffused contamination.Conclusions: Prompt bronchoscopic lavage may be beneficial following large-volume aspiration, potentially through reducing inflammatory mediators and mechanically clearing particulate matter. Despite limitations inherent to its retrospective design and small sample size, this case series supports the safety and clinical utility of bronchoscopic lavage in this setting. Further large-scale studies are warranted to confirm these findings and establish standardized treatment protocols.